Односічний кинджал IV ст. до н. е. з нижнього Подніпров'я - Шелехань, О.В. (Археологія і давня історія України, 2018)
Подано скіфський комплекс IV ст. до н. е. з оригінальним односічним кинджалом північнобалканського типу. In presented article, Scythian barrow with original single-edged dagger is published. This burial is characterized as typical Scythian complex. It was arranged in the catacomb with stone overlap. A buried man was placed with his head to the west, with the dagger near his left hand. This dagger has bright decoration. There were bone plates on the hilt, fixed by three iron rivets with wide heads. Known analogies belong to the horizon of the 5th—4th centuries BC and are associated with impacts from the cultures of the Northern Balkans. Some arrowheads, remained after the robbery, give as possibility to establish the date of this complex more particularly by the middle 4th centuryBC.